(untitled) (Research, Society and Development, 2022)
One of the biggest challenges today is to make companies increasingly competitive, flexible and productive. The current global situation is progressively more intolerant of organizations that are immutable and outdated, as companies cannot be against transformations. Acting through these changes has become something so necessary that it has become a prerequisite for the survival of companies. The present work aims to deal with reengineering as an instrument of change in organizations, considering it as a mechanism for organizational innovation. To this end, qualitative bibliographic research was carried out, selecting articles, books and websites that effectively address the topic. It was concluded that innovation has the possibility of providing competitive benefits in the medium and long term, innovating is fundamental for the support of organizations in the market. Innovation has the ability to increase the value of an organization’s products, distinguishing it from others, being very relevant in markets that have a high level of competition where goods and services are in practice proportional to those of other providers. Thus, those who innovate are at an advantage over others. Still, it is important to analyze that the measure given by the Reengineering process does not contradict itself with the continuous improvement processes, after all, there is a complementarity.